Strategi Pengembangan Karyawan untuk Meningkatkan Kualitas Tahu di UKM Tahu Sumedang : Pendekatan Fishbone - Relita Imelda Veronika; Sella Novyta Sundari; Arrazi Fazrurahman; Muhammad Dimas Tirtawan; Muhammad Al-Farabi Tsani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Reducing product quality is one of the main challenges in the Tofu processing industry, especially in the Sumedang Bumi Armasta Tofu business which is small to medium-scale. The processing, which still maintains the traditional method without the help of technology, has been carried out for many years, but the processing that is still traditional has turned out to cause a dependence on expert employees which if not present will have a direct impact on the quality and quality of the Tofu products produced and the skills of new employees are not optimal in replacing the role of expert employees if they are unable to attend. This study aims to analyze employee development strategies in improving the quality of tofu products using the Fishbone (cause-and-effect) approach. The research method used is qualitative descriptive with data collection techniques through observation and interviews. The results of the analysis show that Human factors (HR) are the main cause of the decline in the quality and quality of Tofu products in Sumedang Tofu SMEs which can be seen from changes in texture, aroma, appearance, and size that are not suitable. Therefore, employee development strategies need to be carried out such as job training, assistance for new employees, and standardization of SOPs that are considered effective in improving the quality of Tofu products to remain consistent.